KONTRIBUSI WALISONGO TERHADAP PERADABAN ISLAM DAN SISTEM PENDIDIKAN ISLAM NUSANTARA - Milla Nuronia; Wilda Imroatul Amalia; Roi Masduki; Anang Sholikhuddin (CV. BAROKAH PUBLISHER, 2026)
This study aims to examine the development of Islamic civilization in the Nusantara during the Walisongo era and its role in shaping the Islamic education system. The novelty of this research lies in the integration of three variables (Islamic civilization, education system, and long-term impact) into a holistic analytical framework, which has not been systematically conducted by previous studies. The method used is qualitative with a descriptive approach through library research, analyzing 20 literatures consisting of 12 accredited journal articles, 6 scientific books, and 2 historical documents. The results show that: Islamic civilization in the Walisongo era developed through cultural acculturation by utilizing arts (wayang, gamelan, tembang) and local traditions as effective da'wah media. Walisongo played an important role in developing pesantren, mosques, and surau as centers for religious learning and character building. The education system developed was flexible, contextual, gradual, and aligned with local wisdom. The conclusion is that Islamic civilization in the Walisongo era not only influenced religious aspects but also became a major foundation for Islamic education in Indonesia today. The practical implication is that the Walisongo-style local culture-based education model can serve as a reference for developing moderate Islamic education in the contemporary era.